Passivity Enhancement Strategy of Grid-Connected Inverter System Based on the Adaptive Active Damper - Shi, Chen; Zhao, Jianfeng (Frontiers in Energy Research, 2022)
The grid-connected inverter system may be unstable when connected to a weak grid, and installing an active damper as a virtual resistor at the PCC is convenient for stabilizing the system. This article proposes a passivity enhancement strategy for the grid-connected inverter system via the adaptive active damper. Furthermore, the admittances of the grid-connected inverter system with the active damper are derived, and the real parts of the admittances of the whole system have been calculated. And the admittance measurement results obtained by the frequency scanning method approximately match the theoretical results. Additionally, the virtual resistor’s stability region is discussed, the bandwidth of the phase-locked loop is recommended, ensuring the stabilizing effect of the active damper under the weak grid. And the online resonance frequency detection algorithm guarantees the passivity enhancement of the active damper when grid impedance changes. Finally, controller hardware-in-the-loop tests validate the theoretical analysis of passivity enhancement based on the active damper.